An analysis and comparison of two German thrust-fencing manuscripts - Noort Reinier van; Schäfer Jan (Bern Open Publishing, 2017)
In this contribution, we will discuss two German fencing manuscripts - Mscr.Dresd.C.13 (SLUB Dresden) and Add MS 17533 (BL London). Both manuscripts present texts on thrust-fencing based on the teachings of Salvator Fabris. The dedication of manuscript C13 was signed by the famous fencing author Johann Georg Pascha. The author of one of the texts contained in the 17533 manuscript is named H.A.V..